Video Project to Enhance Comprehension of TOEIC Material - Fachriyah, Eva; Badriyah, Ratu Dea Mada (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to investigate the application of video project to comprehend TOEIC materials in the